Peran K. H. Mochamad Thowil dalam Pengembangan Sistem Pendidikan di Serang Timur, 1950-2003 - Muhamad Nandang Sunandar; Ahmad Bazari Syam (Departement of History and Islamic Civilization, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2022)
Abstract The growth and development of Islamic education in Indonesia cannot be separated from the process of Islamization carried out by scholars and traders from the Middle East. Islamization in Indonesia through pesantren huts that continue to experience rapid development and is the forerunner of the establishment of formal educational institutions. Pondok pesantren is involved intensely in taking a socio-cultural role which is then used as a reference by the community, one of the boarding schools is the Assalamiyah boarding school which is led directly by KH. Mochamad Thowil, he was born on January 11, 1923 AD. In the village of Wadas district of Lightning Serang district, he had a great obsession in developing Islam, so he founded educational institutions such as madrasahs and boarding schools in 1950. The methods used in research are historical writing methods: Heuristic Stage, Criticism Stage, Interpretation Stage, and Historiographic stage. Based on this research, it can be concluded that KH. Mochamad Thowil acted as a break-in of the education system in the development of Islam and sought to educate the nation. By establishing educational institutions for the Indonesian nation. Along with having a great obsession so he founded educational institutions namely Pesantren and Madrasah.